2014
DOI: 10.1002/chem.201403043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Gd3+‐Based MRI Contrast Agents for Zn2+ Detection: Towards Rational Design

Abstract: A series of novel pyridine-based Gd(3+) complexes have been prepared and studied as potential MRI contrast agents for Zn(2+) detection. By independent assessment of molecular parameters affecting relaxivity, we could interpret the relaxivity changes observed upon Zn(2+) binding in terms of variations of the rotational motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 62 publications
5
32
0
Order By: Relevance
“…Other zinc-sensing conjugates for Gd 3+ that should be mentioned are pyridine-based ligands. Although these sensors worked in vitro, the authors who introduced these agents concluded that they were not suitable candidates for in vivo use because of their low stability and small, non-monotonic response to Zn 2+ [ 61 ]. In addition to Zn 2+ -responsive Gd 3+ -based MR contrast agents, other approaches have been suggested for detecting Zn 2+ in tissues.…”
Section: Detection Of Zinc With Magnetic Resonance Imagingmentioning
confidence: 99%
“…Other zinc-sensing conjugates for Gd 3+ that should be mentioned are pyridine-based ligands. Although these sensors worked in vitro, the authors who introduced these agents concluded that they were not suitable candidates for in vivo use because of their low stability and small, non-monotonic response to Zn 2+ [ 61 ]. In addition to Zn 2+ -responsive Gd 3+ -based MR contrast agents, other approaches have been suggested for detecting Zn 2+ in tissues.…”
Section: Detection Of Zinc With Magnetic Resonance Imagingmentioning
confidence: 99%
“…The first reported agent that could detect Zn 2+ with in vivo application is a manganese porphyrin-derivative, Mn(III)-(DPA-C 2 ) 2 -TPPS 3 , that could detect contrast enhancement in T 1 -weighted images from the hippocampus and the caudate-putamen [40,41]. Subsequently, several gadolinium-based Zn 2+ -responsive CAs have been reported; however, few have made the critical transition from in vitro to in vivo imaging [42][43][44][45]. The typical strategy for zinc-responsive agents is to alter the aminopolycarboxylate macrocyclic ring with a zinc-binding ligand; examples are included in Figure 4.…”
Section: Zinc-responsive Contrast Agentsmentioning
confidence: 99%
“…The relaxivity of the obtained sensor was increased by almost 150 % at high magnetic field B 0 (7.0 T) in the presence of Zn 2+ compared to Ca 2+ and Mg 2+ . Although other strategies for improving Zn 2+ sensing with MRI were proposed, none of the above mentioned sensors have been used in vivo .…”
Section: Mri Sensors To Monitor Zn2+ Ionsmentioning
confidence: 99%